Ubiquitin-mediated control of seed size in plants - Li, Na; Li, Yunhai (Frontiers in Plant Science, 2014)
Seed size in higher plants is an important agronomic trait, and is also crucial for evolutionary fitness. In flowering plants, the seed comprises three major anatomical components, the embryo, the en-dosperm and the seed coat, each with different genetic compositions. Therefore, seed size is coor-dinately determined by the growth of the embryo, endosperm and maternal tissue. Recent studies have revealed multiple pathways that influence seed size in plants. Several factors involved in ubiquitin-related activities have been recently known to determine seed size in Arabidopsis and rice. In this review, we summarize current knowledge of ubiquitin-mediated control of seed size and discuss the role of the ubiquitin pathway in seed size control.